Physico-chemical, photo-catalytic and O-2-adsorption properties of TiO2 nanotubes coated with gold nanoparticles - Malwadkar, Sachin S.; Gholap, Ramkrishna S.; Awate, Shobhana V.; Korake, Prakash V.; Chaskar, Manohar G.; Gupta, Narendra M. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Gold-containing titania nanotubes (Au/NT) were found to display higher activity for photooxidation of acetaldehyde, as compared to corresponding gold-free nanotubes and also a Degussa P-25 catalyst. Besides CO2 as a major reaction product, small amounts of H-2, CH4, CO, H2O and CH3COOH were also formed, irrespective of the catalyst employed. High-resolution TEM examination showed that most of the gold particles in Au/NT were of 1.5-5 nm size, distributed both within and at outside surface of the nanotubes. Some larger size (10-70 run) clusters were also seen at the external surfaces, particularly in the samples calcined at an elevated temperature. The temperature-programmed desorption measurements revealed that, compared to P-25 TiO2, a significant entrapment of O-2 occurred at two distinct tubular sites of NT samples, corresponding activation energy of desorption (E,) being around 36 and 41 kcal mol(-1). On the other hand, gold nanoparticles in Au/NT served as independent low-energy (E-a = 26 kcal mol(-1)) sites for adsorption/activation of O-2. These adsorptive properties of TiO2 and Au were lost completely on calcination, thus revealing a crucial role played by the particle size. In situ IR spectroscopy results showed that room-temperature exposure to acetaldehyde + air gave rise to a molecularly bound state, i.e. CH3CHOad, over both NT and Au/NTsamples, which in turn transformed quickly to yield certain acetate (CH3COOad-) and formate (HCOOad-) type transient species with the involvement of the surface OH groups. The decomposition and oxidation of these surface species with the help of O-2(-), O-ad and hydroxyl ion radicals (OH-) formed at photo-excited Au/NT interfaces led to the reaction products mentioned above. We conclude that, besides electron-hole charge separation, the adsorptive properties of host matrix and nanosize gold may together play a significant role in deciding the photo-catalytic properties of Au/TiO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Acetaldehyde oxidation; Gold co-catalyst; O-2-adsorption; Photo-catalytic activity; TiO2 nanotubes

Enhanced dual-effect of adsorption and photodegradation of SiO2 embedded TiO2 hybrid catalyst for improved decolourization of methylene blue - Sonar, Shilpa K.; Wagh, Reshma V.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Awate, Shobhana V. (Water Air and Soil Pollution, 2013)
Dual-effects of adsorption and photodegradation over titania, silica embedded titania, silica and commercial Degussa P-25 samples were studied for the decolourization of methylene blue in aqueous medium. Silica embedded titania and silica were prepared using inexpensive polymeric version of ethyl silicate as a source of silica. Catalysts were characterized by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and low temperature (77 K) nitrogen adsorption measurements. Among all the catalysts, silica embedded titania has exhibited faster decolourization of methylene blue solution on account of the enhancement of adsorption followed by degradation. An amount of the catalyst and the initial dye concentration of MB solution were found to influence the decolourization activity. Compared to titania catalyst, silica embedded titania and Degussa P-25 have shown the red shift in their UV-Vis spectrum. The experimental data of the reaction fitted well to the pseudo first order kinetic model. In present studies, the adsorption mechanism for the decolourization of MB solution was found to be applicable for an intra particle diffusion model.
Keywords: Adsorption; kinetic model; Methylene blue; Photodegradation; Silica embedded titania

Enhanced mineralization of gaseous organic pollutant by photo-oxidation using Au-Doped TiO2/MCM-41 - Tangale, Nilesh P.; Belhekar, Anuja A.; Kale, Kishor B.; Awate, Shobhana V. (Water Air and Soil Pollution, 2014)
The synthesis, characterization, and photocatalytic evaluation of titania-loaded MCM-41 with and without Au doping are reported in the present study. The samples were characterized by powder XRD, TEM, low temperature N-2 adsorption/desorption, UV-Vis, and FTIR. UV-induced vapor-phase photo-oxidation of acetone was used as a probe reaction to study the role of Au in mineralization of volatile organic compounds (VOCs), viz. acetone at different concentrations. The doping of Au in titania-loaded MCM-41 resulted in the decrease of BET surface area, total pore volume, and average pore size. UV-Vis diffuse reflectance spectra of Au-doped titania-loaded MCM-41 showed the red shift in their absorption bands compared to titania-loaded MCM-41. The activity of mineralization of acetone by photocatalysis for 2 % Au-doped titania-loaded MCM-41 was found to be similar to 1.6 times higher than titania-loaded MCM-41. The presence of cocatalytic nanosized gold might be responsible for their enhanced activity on account of the delayed recombination of electron/hole pair. Although, almost complete mineralization of acetone was observed irrespective of the initial concentration of acetone in air (up to 3.72 mol%) by all the catalysts, 2 wt.% Au-doped titania-loaded MCM-41 has shown the most enhanced activity.
Keywords: Acetone; Doping; Gold; Mineralization of VOCs; Photo-oxidation; TiO2/MCM-41